Зэмос учыр: стихи и рассказы / Эно Рауд - Рауд Эно (Эстон нылпи литература удмурт кылын, 2008)
Экземпляры: М/а ДБ (20090401) / Инвентарный номер: 94169 / Цена: 50.00 / Авт.знак: Р 25 / ГРНТИ: 17.82 / ББК: 84(4Эст)